2014
DOI: 10.1158/1940-6207.capr-13-0320
|View full text |Cite
|
Sign up to set email alerts
|

Slow Overmethylation of Housekeeping Genes in the Body Mucosa Is Associated with the Risk for Gastric Cancer

Abstract: Helicobacter pylori infection increases age-related diverse overmethylation in gene-control regions, which increases the risk of gastric cancer. The H. pylori-associated overmethylation changes subsequently disappear when gastric atrophy and cancer develop. To identify cancer-risk epigenotypes, we traced dynamic methylation changes in the background mucosa of the stomach depending on the extent of gastric atrophy. Paired biopsy specimens were obtained from the noncancerous antrum and body mucosa of 102 patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…Germline inactivation of CDH1, which encodes E-cadherin, is associated with high risk for hereditary diffuse gastric cancer. The site we examined in the CDH1 promoter was previously reported in a cross-sectional study to show methylation changes in the non-malignant antrum adjacent to gastric cancers(23). We also added AMPH and SORCS3, which had been identified from a screen of 14,495 genes, as hypermethylated in both Epstein Barr virus-associated gastric cancers and in uninfected tumors (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Germline inactivation of CDH1, which encodes E-cadherin, is associated with high risk for hereditary diffuse gastric cancer. The site we examined in the CDH1 promoter was previously reported in a cross-sectional study to show methylation changes in the non-malignant antrum adjacent to gastric cancers(23). We also added AMPH and SORCS3, which had been identified from a screen of 14,495 genes, as hypermethylated in both Epstein Barr virus-associated gastric cancers and in uninfected tumors (22).…”
Section: Discussionmentioning
confidence: 99%
“…Pyrosequencing primers for AMPH and SORCS3 were as described in Matsusaka et al(22). Other primer sequences were as follows: for CDH1 : (F) GGTTGTGGTAGGTAGGTGAAT, (R) biotin-AACTTCCCCAAACTCACAAATACTTTAC, (Seq) GTAGGTGAATTTTTAGTTAATTAG, from Oh et al (23); for CDKN2A : (F) TTAGAGGATTTGAGGGATAGGG, (R) biotin-CCCTACCTACTCTCCCCCTCTC, (Seq) GTTGGTTGGTTATTAG; for EMX1 : (F) GTGGGGTTTAGTTTGTTGTATTAAGA, (R) biotin-ATCCCCACCAAACCTCTAAACT, (Seq) TTGAGATTAGGTTTTTTAGAA; for NKX6-1 : (F) GGTTTGGGTGAGTTTATTGAAGATAGT, (R) biotin-CAACCTATACCAACCCCCAAAAT, (Seq) TAGTTTAGAGTTTTTAGGGTAG. Sites of noncommercial assays are shown in Table 1, and maps of CpG locations are shown in Supplementary Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…However, several studies have shown that TFF2 expression was down-regulated pronouncedly in GC compared with the associated normal tissue and promoter hypermethylation at the CpG sites was found to regulate the reduction of TFF2 expression [25,38,76,[83][84][85]. In addition, Oh et al [86] reported that TFF2 gene lacking CpG islands tended to be frequently overmethylated in cancer patients compared with Hp-positive controls. Strikingly increased expression of TFF2 was noted in the diffuse type and advanced stage tumors [82].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus, it represents an objective diagnosis and a potential therapy for gastric cancer. H. pylori infection contributes to the loss of expression of the transcription factor related Runt-3 (RUNX3) in gastric cancer through its overmethylation (69). …”
Section: Epigenetic Changes Promote the Development Of Gastric Cancermentioning
confidence: 99%